Inference in economic experiments - Norbert Hirschauer; Sven Grüner; Oliver Mußhoff; Claudia Becker (Economics: The Open-Access, Open-Assessment E-Journal, 2020)
Replication crisis and debates about p-values have raised doubts about what we can statistically infer from research findings, both in experimental and observational studies. With a view to the ongoing debate on inferential errors, this paper systematizes and discusses experimental designs with regard to the inferences that can and - perhaps more important - that cannot be made from particular designs.
Keywords: B41; C18; C90; 330; economic experiments; ceteris paribus; confounders; control; inference; internal/external validity; randomization; random sampling; superpopulation